PERKEMBANGAN TRANSPORTASI ONLINE: GOJEK DI KOTA PADANG 2017-2019 - Elva Damayanti; Zulfa; Juliandry Kurniawan Junaidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the development of GOJEK’s online transportation services in Padang City during the 2017–2019 period as part of an urban mobility transformation influenced by digital technological advancements. The emergence of GOJEK marked a significant shift in the local transportation system by offering services perceived as more practical, efficient, and transparent compared to conventional modes such as public minivans and base motorcycle taxis. The objectives of this research are to: (1) describe the dynamics of GOJEK’s service development in Padang City, (2) analyze the social and economic impacts arising from its presence, and (3) identify the responses of the community and local government to the introduction of app-based transportation. The research employs the historical method, including heuristics, source criticism, interpretation, and historiography, supported by observation, literature review, and interviews with driver-partners and service users. The findings indicate that GOJEK experienced rapid growth from the early stage of its operations, reflected in the increasing number of driver-partners, expansion of service features, and rising public interest. Positive impacts include improved accessibility, greater travel-time efficiency, and the creation of new employment opportunities. However, the development also generated challenges, including resistance from conventional transportation operators, social conflicts, and limitations in local regulations that had not fully accommodated online transportation at the time. Overall, the development of GOJEK in Padang City illustrates the process of urban community adaptation to technological innovation while highlighting the need for policy adjustments at the local level.